Sclerostin and osteoprotegerin: new markers of chronic kidney disease mediated mineral and bone disease in children - ALPAY, HARİKA; GÖKCE, İBRAHİM (WALTER DE GRUYTER GMBH, 2020)
Background: Sclerostin and osteoprotegerin (OPG) are new markers of chronic kidney disease (CKD) mediated mineral bone disease (CKD-MBD) which were extensively evaluated in adult population. We aimed to evaluate the associations between serum levels of sclerostin/OPG and parameters of bone turnover and compare the serum levels of sclerostin/OPG in different stages of CKD in children. Methods: 70 children with CKD stage 1-5, aged 2-21 years were examined. Serum levels of alkaline phosphatase (ALP), creatinine, total calcium, phosphorus , intact parathyroid hormone (iPTH) and vitamin D were measured. Serum sclerostin and OPG levels were measured in children with different levels of CKD stage and their association with bone turnover parameters were noted. Results: We did not observe any significant correlation between serum levels of sclerostin and OPG and stages of CKD. A negative relationship was present between serum sclerostin and 25-OH vitamin D levels. Osteoprotegerin was positively and significantly correlated with ALP but serum sclerostin was negatively correlated with ALP. Conclusion: Our study, which includes only children and adolescents with a growing skeleton under uremic conditions and excluding diabetes and atherosclerosis interference, is very valuable. We couldn't find any significant relationship between either sclerostin or OPG levels among different stages of CKD. Also our study demonstared a strong negative relationship between ALP and sclerostin levels and a strong positive relationship between ALP and OPG levels, reminding the importance of ALP levels to predict the bone-mineral status of the children with CKD.
Keywords: alkaline phosphatase; child; chronic kidney disease; mineral-bone disease; osteoprotegerin; sclerostin; SERUM SCLEROSTIN; GROWTH